Implikasi Hukum Penyalahgunaan Narkotika oleh Anak di Bawah Umur terhadap Ketahanan Nasional di Sulawesi Selatan - Al Hadana, Farid; Firamulia, Muhammad Tryas Budi; Sukarman; Margono, Farhan; Fahri, Marjana (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2025)
Drug abuse by minors is a multidimensional problem that significantly impacts national resilience. This study aims to examine the legal and strategic implications of child involvement in drug abuse, with a geographic focus on South Sulawesi Province. This study highlights the effectiveness of law enforcement, the implementation of rehabilitation policies, and the social challenges faced in fostering the younger generation as the foundation of national resilience. Using a juridical-normative and sociological approach, this study analyzes the applicable legal framework, specifically Law No. 11 of 2012 concerning the Juvenile Criminal Justice System and Law No. 35 of 2009 concerning Narcotics, as well as the dynamics of their implementation at the local level. The study’s findings indicate that drug abuse in South Sulawesi is concentrated among productive-age males in urban areas with secondary education and involvement in the informal sector, with children in this vulnerable environment. Although the legal framework formally positions children as victims entitled to diversion, rehabilitation, and exceptional protection, law enforcement practices are still dominated by repressive approaches, limited use of restorative justice, and weak inter-agency coordination. Structural constraints, including budget constraints, inadequate facilities, overlapping authority with the police, information leaks, and strong social stigma, significantly hamper the effectiveness of rehabilitation and social reintegration of child victims of drug abuse. From a national resilience perspective, these weaknesses could create an alienated and unproductive generation. This article emphasizes that an integrated penal and non-penal strategy centered on the best interests of children and community-based prevention is a crucial prerequisite for strengthening national resilience in the face of the threat of narcotics.